PEMANFAATAN LIMBAH TEMPURUNG KELAPA DAN GETAH NANGKA DALAM PEMBUATAN BIOBRIKET - Rahman, Hairul; Priyagung Hartono; Mochammad Basjir (Universitas Islam Malang, 2023)
ABSTRACTBiomass is material obtained from plants, either directly or indirectly, and used as energy or materials in large quantities. Using plantation waste, namely coconut shells which will be processed into solid fuel, namely (briquettes). The coconut shell is carbonated into charcoal which will be mashed into a charcoal surge with mesh size 40, mesh 60 and mesh 80. Using charcoal powder as much as 28 grams, 26 grams, and 22 grams which will be mixed with nagka sap as much as 7 grams, 8 grams, and 12 grams. Briquettes are printed using hollow iron with a size of 3x3 cm and will be dried in the sun for 4 days of drying. Test parameters include moisture content test, combustion rate test, calorific value test. The results showed that the briquettes in mesh 80 with the addition of jackfruit sap adhesive of 28 grams of charcoal and 8 grams of jackfruit sap had the best calorific value of 6643.84 ccal/grammwith a burningg rate of 0.221 grams/minutee and a moisture content of 8.71%.Keywords : Biomass, Briquettes, Coconut Shell, Jackfruit Sap